2023
DOI: 10.1186/s12889-022-14974-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hypertension in the last 16 years in high prevalence region of China and the attribute ratios for cardiovascular mortality

Abstract: Background Tianjin is one of the cities with the highest prevalence of hypertension in China and one of the first regions to develop community management of hypertension. Our aim was to analyze the characteristics of hypertension in the last 16 years, and estimate the population attributable fraction for cardiovascular mortality in Tianjin, China. Methods We compared the epidemiological characteristics of hypertension between 2002 and 2018 by analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[16] Previous data have shown that hypertension is listed first in prevalence among 5 chronic diseases in Tianjin, [17] and the prevalence of hypertension in the coastal area is at a high level. [16,18] Compared with previous studies conducted in this area, [17,19] our data indicate that the prevalence of hypertension in 2022 is much higher than that in 2018 (39.8%) [20] and in 2015 (32.7%). [21] Variations in the levels of risk factors for hypertension, such as high sodium intake, low potassium intake, obesity, alcohol consumption, physical inactivity, and unhealthy diet, may explain some of this increase.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[16] Previous data have shown that hypertension is listed first in prevalence among 5 chronic diseases in Tianjin, [17] and the prevalence of hypertension in the coastal area is at a high level. [16,18] Compared with previous studies conducted in this area, [17,19] our data indicate that the prevalence of hypertension in 2022 is much higher than that in 2018 (39.8%) [20] and in 2015 (32.7%). [21] Variations in the levels of risk factors for hypertension, such as high sodium intake, low potassium intake, obesity, alcohol consumption, physical inactivity, and unhealthy diet, may explain some of this increase.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, compared with results from the same period in Beijing (52.6%, 50.4%, 23.9%), [40] the awareness, treatment, and control of hypertension in the coastal areas of Tianjin were also better. Although the rates improved greatly compared with previous years and other regions, [18,[20][21][22][23] the results nonetheless mean that nearly 10% of hypertension was underestimated in the participants, about 20% of hypertension was untreated, and approximately one-half of hypertension was uncontrolled. Health authorities should note that comprehensive methods should be included for hypertension management in the community population.…”
Section: Discussionmentioning
confidence: 81%
“…Hypertension has emerged as the primary risk factor for cardio-cerebrovascular disease ( 4 ). Due to the widespread adoption of unhealthy lifestyles resulting from rapid economic development and the accelerated aging process, hypertension has witnessed an increase in low- and middle-income countries, including China ( 5 ). According to recent survey data from China, the prevalence of hypertension among individuals aged 18 years from 2012 to 2015 reached a significant rate of 27.9% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cerebrovascular disease ranks as the second most lethal ailment on a global scale, and acute cerebrovascular disease exhibits a higher incidence of disability compared to any other individual disease, thereby imposing substantial societal burdens (3). Hypertension has emerged as the primary risk factor for cardiocerebrovascular disease (4). Due to the widespread adoption of unhealthy lifestyles resulting from rapid economic development and the accelerated aging process, hypertension has witnessed an increase in low-and middle-income countries, including China (5).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, or high blood pressure, is a prevalent and significant public health issue among older adults worldwide, posing a considerable burden on healthcare systems and leading to various adverse health outcomes, including stroke (1), heart failure (2), renal diseases (3), and mortality (4). The aging process is often associated with physiological changes that can contribute to the development of hypertension, making older individuals, especially those over 80 years of age, particularly susceptible to this condition (5).…”
Section: Introductionmentioning
confidence: 99%